RdxA-independent mechanism of Helicobacter pylori metronidazole metabolism - Zhao, Yakun; He, Lihua; Sun, Lu; Liu, Wentao; Wang, Hairui; Zhang, Jianzhong; Gong, Yanan; Wang, Xiaohui (Frontiers in Microbiology, 2025)
IntroductionMetronidazole (MNZ) is widely used to treat Helicobacter pylori infection worldwide. However, due to excessive and repeated use, resistance rates have exceeded 90% in some regions. The mechanisms of MNZ resistance have been extensively studied, and RdxA has been identified as the primary enzyme responsible for MNZ activation. Mutations in RdxA, particularly termination mutations, can lead to high-level MNZ resistance.MethodsWe identified a strain, ICDC15003s, which harbored RdxA termination mutation but remained highly susceptible to MNZ. To explore this phenomenon, we conducted comparative genomic and transcriptomic analyses to define RdxA-independent mechanisms of MNZ metabolism.Results and discussionWe found missense mutations in genes such as yfkO, acxB, alr1, glk, and cobB. Additionally, the expression of multiple genes, including TonB-dependent receptor and mod, significantly changed in resistant strains. Notably, the sequences and expression levels of known nitroreductases like FrxA and FdxB remained unchanged after induction of MNZ resistance, suggesting they were not responsible for MNZ sensitivity in ICDC15003s. Instead, transcriptional alterations were observed in genes encoding NADH-quinone oxidoreductase subunit (M, J, H and K), suggesting a potential compensatory mechanism for the loss of RdxA activity. We proposed that NADH-quinone oxidoreductase might serve as an RdxA-independent mechanism for MNZ metabolism and resistance through regulation of its expression levels. This discovery could provide new strategies to address MNZ resistance and aid in developing nitroimidazole antibiotics.